2001
DOI: 10.1046/j.1365-2273.2001.00475.x
|View full text |Cite
|
Sign up to set email alerts
|

Interleukins 7 and 12 are expressed in head and neck squamous cancer

Abstract: Interleukin 7 (IL-7) and IL-12 have major roles in cell-mediated tumour immunity. In head and neck squamous cell cancer, depressed cell-mediated immunity is well documented and may account for the poor prognosis. This is the first study to assess intratumour expression of IL-7 and IL-12 in head and neck squamous cell cancer (HNSCC). Immunohistochemistry was used to identify IL-7 and IL-12 expression in snap-frozen tumour specimens from 25 patients with HNSCC and the results of immunohistochemical staining were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Multivariate survival analysis even suggested that IL-12 should be a negative independent prognostic factor besides T stage and MVD, which was contrary to our initial expectation. Paleri and his colleagues assessed intratumoral expression of IL-12 and IL-7 in head and neck squamous cell cancers (HNSCC), and proved a trend towards better survival associated with high expression of IL-12 [8] . There could be variable antitumor immune mechanisms in tumors with different origin and different pathologic type, and IL-12 seemed not to take participate in antitumor immunity of gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Multivariate survival analysis even suggested that IL-12 should be a negative independent prognostic factor besides T stage and MVD, which was contrary to our initial expectation. Paleri and his colleagues assessed intratumoral expression of IL-12 and IL-7 in head and neck squamous cell cancers (HNSCC), and proved a trend towards better survival associated with high expression of IL-12 [8] . There could be variable antitumor immune mechanisms in tumors with different origin and different pathologic type, and IL-12 seemed not to take participate in antitumor immunity of gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Disease-free survival correlated with a poorer prognosis when head and neck squamous cell carcinoma simultaneously produced 3 or more growth factors. Paleri et al 39 examined the production of IL-12 protein in head and neck squamous cancer. Those authors did not find a significant correlation between IL-12 and disease-free survival.…”
Section: Discussionmentioning
confidence: 99%
“…IL-7 has been demonstrated to affect cell growth and survival in certain haematological malignancies, including acute lymphoblastic leukaemia ( 37 39 ), cutaneous T cell lymphoma ( 20 , 40 , 41 ), Hodgkin's disease ( 42 ), acute myeloid leukaemia ( 43 ) and chronic lymphocytic leukaemia ( 39 , 43 , 44 ). IL-7 mRNA has also been identified in numerous solid organ tumours, including Warthin's tumour of the parotid gland ( 45 ), head and neck squamous cell carcinomas ( 46 ), renal cell carcinoma ( 47 ), oesophageal carcinoma ( 48 ), colorectal carcinoma ( 49 ) and breast carcinoma ( 19 ). The exact role of IL-7 in these tumours is not fully understood, however it is thought to affect lymphocytes ( 49 ); for instance, in cutaneous T-cell lymphoma, IL-7 has been shown to support the growth of malignant T-cells in the skin ( 21 ).…”
Section: Introductionmentioning
confidence: 99%